PERSONALITY TYPOLOGIES OF MODERN SCHOOL TEACHERS AND THEIR PEDAGOGICAL IMPLICATIONS (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article provides a conceptual and analytical overview of typological characteristics of a modern school teacher’s personality and explains why a typological perspective remains practically important for contemporary education. The study interprets “teacher personality typology” as an integrative description of relatively stable traits, motivational orientations, emotional-regulatory patterns, and communication styles that influence pedagogical decisions, classroom climate, and professional resilience. Drawing on widely used personality frameworks (trait approaches, temperament concepts, and socio-cognitive perspectives), the paper proposes a structured view of typological profiles relevant to school practice: learner-centered facilitator, structured organizer, emotionally responsive mentor, reflective analyst, and innovation-oriented change agent. The article argues that typological differences are not “good or bad” in themselves; their educational value depends on professional competencies, ethical standards, and the match between teacher style, student needs, and school context. Practical implications for teacher education and professional development include diagnostic reflection, individualized training trajectories, communication skills, self-regulation strategies, and the prevention of professional burnout. The paper concludes that typological analysis can support evidence-informed mentoring and align teaching styles with contemporary competency-based and inclusive education goals, while maintaining respect for individual differences.